PENGARUH KATALIS BENTONIT PADA HASIL VOLUME SYNGAS GASIFIKASI LIMBAH KAYU GALAM DAN BATUBARA KUALITAS RENDAH - Ahmad Fitrianor; Aqli Mursadin (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2019)
This study aims to determine and compare the results of the syngas volume generated from variations in mixing of galam wood powder and bentonite catalyst coal. This research was carried out by mixing galam wood powder and coal with a mass of 200g which was given a bentonite catalyst. There were 4 variations of mixing ingredients namely 200g galam wood powder and 0g coal, 180g galam wood powder and 20g coal, 140g galam wood powder and 60g coal, 100g galam wood powder and 100g coal which added 50%, 30% and 10% bentonite catalysts from the mass of material in each variation of the temperature. Material in updraft gasification with a temperature of 500oC for 120 minutes or 2 hours. The results showed that variations with a mixture of 200g of galam wood powder and 0g coal were the ones that produced the most syngas. This was due to the density of galam wood powder which was more tenuous so it was more flammable at temperatures up to 500oC. The amount of bentonite catalyst addition also affects the volume of syngas produced, where the more addition of bentonite catalysts the more syngas volume is produced, this is because bentonite contains Al2O3 which has good heat conductivity so the heating rate is faster, due to the heating rate faster makes the syngas volume produced more for 120 minutes when gasification.